Change the name of your Android device - rosari J (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2019)
We'll learn how to modify the name of an Android device in device settings in this tutorial. In addition, we'll show you how to alter the WiFi Direct and Hotspot network names, as well as the Bluetooth connection name, on Android devices.For sharing internet data and transferring files from one device to another, Wi-Fi and Bluetooth are the most often utilized ways of connectivity on smartphones. When you use your Android phone or tablet to scan for a Wi-Fi or Bluetooth connection, you'll see either a generic or personalized name for the identified devices. If you're new to Android, this quick guide will show you how to give your phone or tablet a unique name that will appear when other devices search for it. Let's look at how to modify the name of a WiFi, Bluetooth, mobile hotspot, or tethering device.Setting up a device name for WiFi and Bluetooth connections is straightforward, which is why I call it a beginner's instruction. Please don't go any farther if you're an experienced Android user. All of the choices are already available in the phone settings; I'll just show you how to access them.